2021
DOI: 10.1111/jcms.13266
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the European Semester: Case Study Analysis and Lessons for its Post‐Pandemic Transformation*

Abstract: This paper examines whether and how the European Semester has influenced structural reforms in member states. It does so by analysing the interaction between the Commission and the national bureaucratic and political levels. The paper presents two process‐tracing exercises with a focus on those actors that directly worked with the CSRs to assess the political dynamics underpinning the CSR implementation process. First, it examines the more nuanced and indirect effects the Semester had on the liberalization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…Moreover, implementation depended on several factors, resulting in variable influence on national policy reforms (Bokhorst, 2022; Mariotto, 2022; Efstathiou and Wolff, 2019). In a comparative study of social CSRs, Al-Kadi and Clauwaert (2019) showed that ‘tinderbox’ policies such as wages and pensions were less likely to be the object of reform.…”
Section: Limits and Opportunities Of The European Semestermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, implementation depended on several factors, resulting in variable influence on national policy reforms (Bokhorst, 2022; Mariotto, 2022; Efstathiou and Wolff, 2019). In a comparative study of social CSRs, Al-Kadi and Clauwaert (2019) showed that ‘tinderbox’ policies such as wages and pensions were less likely to be the object of reform.…”
Section: Limits and Opportunities Of The European Semestermentioning
confidence: 99%
“…Bokhorst (2022) contends that assessing the Semester only through its impact on national policy is misleading. The influence is more cognitive and seldom direct: ‘(b)y continuously confronting the domestic actors with evidence and demanding a response in return, (the Semester) makes it harder to ignore pressing issues.’ This stems from the rational-legal authority of European bureaucracy, which socializes national actors through ‘the iterative use of EU concepts, categories, and metrics in formulating and reviewing Member States’ plans for achieving common objectives’ (Zeitlin, 2009: 227).…”
Section: A Supranational Response: Closing the Evaluation Cyclementioning
confidence: 99%
“…The nature of these recommendations feeds into the question of whether different wage-setting regimes and labour market types are associated with heterogenous economic outcomes, which is a topic that has been subject to considerable debates in the EU's political economy literature (Johnston, 2016; Nölke, 2016). Höpner and Lutter (2018) have, for instance, found that decentralized wage-setting institutions are associated with higher wage inflation, whereas centralized and corporatist labour relations regimes tend to have lower wage inflation. The different outcomes that different constellations of wage-setting regimes give rise to has even led some scholars to question the compatibility of different wage-setting regimes and labour market institutions in a common currency area (Johnston and Regan, 2016).…”
Section: European Integration Wage-setting Regimes and The Eurozone C...mentioning
confidence: 99%
“…Second, even when not binding, CSRs can have an indirect impact on member states' reforms initiatives. CSRs on labour market flexibilization and wage-setting have, for example, had an important impact in the domestic political agenda of labour market reforms in Belgium, France and Italy (Bokhorst, 2022;Syrovatka, 2021b). Although the exact nature of the mechanisms through which member states comply with CSRs constitutes a burgeoning area of research (Guardiancich and Guidi, 2020), CSRs have often found to have had a significant impact on national reform programs.…”
Section: The European Semester and The Role Of The Commissionmentioning
confidence: 99%
See 1 more Smart Citation